(untitled) (Fiep Bulletin - online, 2011)
This article is part of a doctoral thesis begun in 2006 at the Vila Vicentina Júlia Freire nursing home in João Pessoa, Brazil. The aim was to follow and record the life and behavior of the residents, in relation to their personal life, socialization and way of living, with an emphasis on body image. In this perspective, we chose the narrative interview model, using techniques that allowed us to obtain the maximum of information from the subjects. Respecting the freedom and independence of the narrative report, we encouraged them to reveal as much as possible about their lives, taking into consideration the subjects’ line of thinking and the personal chronology of the residents. The method consisted of six steps, with four phases: preparation, initiation phases, main narration, questioning, conclusive discourse and finally the construction of a memory protocol from which we selected the topics shared by all the discourses such as: what the elderly individuals of a nursing home think of themselves, in relation to their body, to others and to the idea of quality of life, that is: a. the elderly as seen by themselves and by others; b. religiosity as a moral factor; c. intimacy and relationships. The criteria for choosing the aforementioned categories were based on the relevance of the themes raised by the subjects. In this article, we included only the narratives that dealt with the third category in the daily life of the elderly residents.